A CV Study of Copper Complexation with Guanine Using Glassy Carbon Electrode in Aqueous Medium. (2nd April 2014) - Rana, Md. Sohel; Rahman, Mohammad Arifur; Alam, A. M. Shafiqul
Abstract : Voltammetric behaviors of Copper (II) nitrogen bearing nucleobases, such as Guanine (C5 H4 N5 O2 ) was studied in electro analyzer using cyclic voltammetry (CV) on a Glassy Carbon Electrode. Assessment of the chemical and physical conditions that may favor optimum current enhancement was done by studying the effect of variation of concentration of metal and ligand ions, variation of scan rate, variation of step height, variation of pH values, and variation of supporting electrolyte as (NH4 )2 SO4, KCl, and NaCl. It was observed that Copper and Guanine forms a 1 : 2 ratio complex. The work reflects that increasing the concentration of either metal ion or ligand ion increases the corresponding current. Increasing the scan rate increases the corresponding current linearly with the square root of the scan rate. As the step height decreases the peaks become sharp. Anodic and cathodic current increases linearly with decreasing step height. For the complex mixture the complexation occurs maximum at a pH of 2.3–7.0 and is badly restricted in the slightly alkaline medium and the complexing order of the supporting electrolyte showed a trend as ( N H 4 ) 2 S O 4 > N a C l > K C l .